LINKING RELIGIOSITY TO SOCIO-ENTREPRENEURSHIP INTENTION: A CASE OF MUSLIM YOUTH - Annes Nisrina Khoirunnisa; Uma Zalfa Salsabiil; Fajar Sodik; Nala Syifa Dewanti; Rizaldi Yusfiarto (Bank Indonesia, 2023)
Using an integrated entrepreneurial model, this study examines social entrepreneurship intention of Muslim youth in Indonesia. In the study, a total of 206 Muslim youths is surveyed and the data are analyzed using the partial least squares structural equation model (PLS-SEM). The findings show that, while religiosity does not have a direct effect on socio-entrepreneurial intention, it increases perceived desirability. We reason that the religiosity of Muslim youth is more on the formation of positive perceptions, which give rise to desires and intentions to be socio-entrepreneurs. Thus, the application of social entrepreneurship among Muslim youth in Indonesia is supported by not only profits but also individual beliefs in creating social value and prospering society.